1993
DOI: 10.1128/jb.175.3.716-722.1993
|View full text |Cite
|
Sign up to set email alerts
|

Effects of consecutive AGG codons on translation in Escherichia coli, demonstrated with a versatile codon test system

Abstract: A system for testing the effects of specific codons on gene expression is described. Tandem test and control genes are contained in a transcription unit for bacteriophage T7 RNA polymerase in a multicopy plasmid, and nearly identical test and control mRNAs are generated from the primary transcript by RNase III cleavages.Their coding sequences, derived from T7 gene 9, are translated efficiently and have few low-usage codons of Escherichia coli. The upstream test gene contains a site for insertion of test codons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(144 citation statements)
references
References 28 publications
5
137
1
1
Order By: Relevance
“…Conversely, if they increased the concentrations of cognate tRNA, then the A-site vacancy time was reduced and the frameshift frequency dropped. The aforementioned results are consistent with those of Rosenberg et al (1993), who found that mRNA containing high numbers of the rare codon AGG caused its corresponding tRNA to be sequestered and the ribosome stalled at the first of two consecutive AGG codons. The stalled ribosome frameshifted, hopped, or terminated translation as an upstream translating ribosome approached.…”
Section: Introductionsupporting
confidence: 81%
“…Conversely, if they increased the concentrations of cognate tRNA, then the A-site vacancy time was reduced and the frameshift frequency dropped. The aforementioned results are consistent with those of Rosenberg et al (1993), who found that mRNA containing high numbers of the rare codon AGG caused its corresponding tRNA to be sequestered and the ribosome stalled at the first of two consecutive AGG codons. The stalled ribosome frameshifted, hopped, or terminated translation as an upstream translating ribosome approached.…”
Section: Introductionsupporting
confidence: 81%
“…However, we propose that these two slowly translated codons are avoided by slow regions (that occur at mRNA spans that correspond to the strategic positions on proteins such as domain ends) because they may induce dissociation of the translation complex and cause a deleterious rather an intentional pause. Many reports in the literature (Robinson et al, 1984;Bonekamp et al, 1985;Spanjaard & van Duin, 1988;Varenne et al, 1989, Chen & Inouye, 1990Spanjaard et al, 1990;Kinnaird et al, 1991;Rosenberg et al, 1993;Goldman et al, 1995) show that the introduction of cua (Leu) or agg (Arg) codon strings results in the reduction of protein yield and presumably induces dissociation of the translation complex or frameshifting and hopping (Kane et al, 1992) events. Chen and Inouye (1990) observed preferential use of such codons in the region spanning the first 25 codons of the mRNA; they suggest that such a preference for the minor codons in an early gene section may modulate gene expression by premature termination of translation, thereby avoiding unnecessary translation of a large part of the mRNA.…”
Section: Rare Codons and Their Usage In Slow Regionsmentioning
confidence: 99%
“…We chose to study the rare Arg codons AGA and AGG [termed "AGR" according to International Union of Pure and Applied Chemistry (IUPAC) conventions] because the literature suggests that they are among the most difficult codons to replace and that their similarity to ribosome-binding sequences (RBSs) underlies important noncoding functions (8,(27)(28)(29)(30). Furthermore, their sparse use (123 instances in the essential genes of E. coli MG1655 and 4,228 instances in the entire genome) ( Table 1 and Dataset S1) made replacing all AGR instances in essential genes a tractable goal, with essential genes serving as a stringent test set for identifying any fitness impact from codon replacement (31).…”
Section: Significancementioning
confidence: 99%